Multi-wavelength optical imaging of human tumour xenografts - Wang, Wei (2011)
In vivo optical imaging methods have become a cornerstone of pre-clinical cancer research. Genetically modified cells with fluorescent or bioluminescent reporters allow researchers to non-invasively study tumour proliferation and biochemistry over time. Target-specific fluorescent probes may be used to reveal specific tumour properties such as growth patterns, neovasculature formation, and compartmental probe absorbance. Herein, we demonstrate the simultaneous optical imaging of these tumour properties in a human neuroblastoma model. We used luciferase-positive cancer cells, a neovasculature specific fluorescent probe, and a fluorescent tumour cell target-specific agent, in conjunction with X-ray/CT for anatomical localization. These experiments revealed a detailed map of the tumour progression and biological interactions with imaging agents within the tumour.